Coaching in Surgical Education: A Systematic Review - Louridas, Marisa; Sachdeva, Ajit K; Yuen, Andrew; Blair, Patrice; MacRae, Helen (Annals of surgery, 2022)
The objectives of this study were to review the coaching literature to (1) characterize the criteria integral to the coaching process, specifically in surgery, and (2) describe how these criteria have been variably implemented in published studies. Coaching is a distinct educational intervention, but within surgery the term is frequently used interchangeably with other more established terms such as teaching and mentoring. A systematic search was performed of the MEDLINE and Cochrane databases to identify studies that used coach/coaching as an intervention for surgeons for either technical or nontechnical skills. Study quality was evaluated using the Medical Education Research Study Quality Instrument (MERSQI). A total of 2280 articles were identified and after screening by title, abstract and full text, 35 remained. Thirteen coaching criteria (a-m) were identified in 4 general categories: 1. overarching goal (a. refine performance of an existing skill set), 2. the coach (b. trusting partnership, c. avoids assessment, d. 2-way communication), the coachee (e. voluntary participation, f. self-reflection, g. goal setting, h. action plan, i. outcome evaluation), and the coach-coachee rapport (j. coaching training, k. structured coaching model, l. non-directive, m. open ended questions). Adherence to these criteria ranged from as high of 73% of studies (voluntary participation of coach and coachee) to as low as 7% (use of open-ended questions). Coaching is being used inconsistently within the surgical education literature. Our hope is that with establishing criteria for coaching, future studies will implement this intervention more consistently and allow for better comparison and generalization of results.